A dialogue with Dr Mohammad Rostami Nejad - Makovicky, Peter (International journal of celiac disease, 2017)
We are continuing to journal interview and today Dr Mohammad Rostami Nejad from Gastroenterology and Liver Diseases Research Center of Shahid Beheshti University of Medical Sciences, Tehran, Iran is asked.
Keywords: bezlepková dieta; Celiac Disease; Írán; Iran; Diet, Gluten-Free; celiakie